Social media-driven antecedents and consequences of employees' awareness of their impact on corporate reputation - Schaarschmidt, Mario; Walsh, Gianfranco (Journal of business research, 2020)
When employees use social media, their behavior can be attributed to their employer, thereby shaping the company's reputation in the eyes of various stakeholders. Thus, employees are well advised to use social media in a way that does comply with social norms in social media to avoid reputational damage for their firm. However, research has been anemic to the drivers of appropriate employee social media behavior. This research combines organizational behavior research related to employee engagement and reputation with work concerning employees and social media to arrive at a model that relates the firm's social media appearance with appropriate employee social media behavior. Central to this model is employees' awareness that they can shape their employer's online reputation. Based upon two quantitative studies, this research tests a model of social media-related antecedents and consequences of employees' awareness of their impact on corporate reputation, and discusses managerial and theoretical implications.